2015
DOI: 10.1002/2014jg002872
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost thaw and soil moisture driving CO2 and CH4 release from upland tundra

Abstract: As permafrost degrades, the amount of organic soil carbon (C) that thaws during the growing season will increase, but decomposition may be limited by saturated soil conditions common in high-latitude ecosystems. However, in some areas, soil drying is expected to accompany permafrost thaw as a result of increased water drainage, which may enhance C release to the atmosphere. We examined the effects of ecosystem warming, permafrost thaw, and soil moisture changes on C balance in an upland tundra ecosystem. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
170
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 69 publications
17
170
3
Order By: Relevance
“…Resiliency functions and services include flood storage, buffering of storm damage, protecting water quality by filtering pollutants and sediment out of runoff generated by severe storm events, groundwater recharge and provision of water supply during drought, provision of wildlife refuges and corridors and maintenance of biodiversity (Junk et al 2013; Association of State Wetland Managers 2015a; Narayan et al 2016), regulating microclimate (Zhang et al 2016) and physically buffering coasts from sea level rise and increases in storm surges (Millennium Ecosystem Assessment 2005), as well as others enumerated elsewhere in this article. Anderson et al (2016a) state, BProtecting wetlands and riparian corridors has been suggested as one of the single best actions in promoting resilience and in sustaining biodiversity (Naiman et al 1993, Fremier et al 2015)^.…”
Section: Part 2: Emerging Policies and Management Strategies For Protmentioning
confidence: 99%
“…Resiliency functions and services include flood storage, buffering of storm damage, protecting water quality by filtering pollutants and sediment out of runoff generated by severe storm events, groundwater recharge and provision of water supply during drought, provision of wildlife refuges and corridors and maintenance of biodiversity (Junk et al 2013; Association of State Wetland Managers 2015a; Narayan et al 2016), regulating microclimate (Zhang et al 2016) and physically buffering coasts from sea level rise and increases in storm surges (Millennium Ecosystem Assessment 2005), as well as others enumerated elsewhere in this article. Anderson et al (2016a) state, BProtecting wetlands and riparian corridors has been suggested as one of the single best actions in promoting resilience and in sustaining biodiversity (Naiman et al 1993, Fremier et al 2015)^.…”
Section: Part 2: Emerging Policies and Management Strategies For Protmentioning
confidence: 99%
“…Over the past two decades, several studies have documented the effect of an experimental manipulation of soil hydrologic conditions on biogeochemical cycles in Arctic ecosystems (e.g., Oechel et al, 1998;Olivas et al, 2010;Natali et al, 2015). Only a few of these studies examined longterm effects of manipulated water tables (e.g., Christiansen et al, 2012;Lupascu et al, 2014;Kittler et al, 2016), and none of them explicitly addressed the net impact of hydrologic disturbance on the energy budget; only shifts in thaw depth (Zona et al, 2011a;Kim, 2015) and indirect effects of heat fluxes on the carbon cycle (Turetsky et al, 2008) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Their sustainability relies on the integrity of perennially frozen ground that provides permanent or seasonal water supply and prevents vertical percolation (Woo 2012;Natali et al 2015). However, observations over the last decades indicate that permafrost thawing and active layer deepening, closely related to the ratio of ground ice content and ground thermal conditions (Burn and Kokelj 2009;Kanevskiy et al 2013;Rudy et al 2017), have intensified with increasing temperatures (Romanovsky et al 2010;Rowland et al 2010;Liljedahl et al 2016;Vincent et al 2017).…”
Section: Introductionmentioning
confidence: 99%